School Pastoral in Preparation for Priesthood Duties: Strengthening the Pedagogical and Spiritual Competence of Students of the Faculty of Philosophy - Laurentius Tinambunan (Abdimas Paspama, 2023)
School pastoral is an important part of the formation of prospective priests because it brings together the learning of philosophy and theology with concrete experience accompanying students. This Community Service activity was carried out in the context of the Education and Student Orientation (ORDIK) for new students of the Faculty of Philosophy, Catholic University of Saint Thomas on August 7-11, 2023. The material